Governing Abroad : Coalition Politics and Foreign Policy in Europe - Oktay, Sibel (Book collections on Project MUSE., 2022)
From Austria to New Zealand, coalition governments often pave the road to foreign policy. In Western Europe, nearly 90 percent of postwar governments include two or more political parties. Israel, the Middle East's only consolidated democracy according to many, has never experienced single-party rule in its history. Even the United Kingdom, known for its long streak of single-party rule, now navigates multiparty cabinets. Coalitions are everywhere, but we still have little understanding of how they act in foreign affairs. History shows that coalitions can sometime engage in powerful international commitments such as participating in military operations, but at other times, they postpone their decisions, water down their policy positions, or promise to do less than they otherwise would. What explains these differences in behavior?Governing Abroad unpacks the little-known world of coalition governments to find out. Oktay argues that the specific constellation of parties in government explains why some coalitions can make more assertive foreign policy decisions than others. Building on the rich literatures in political science on coalitions, legislatures, and voting behavior, the book weaves together sophisticated statistical analyses of foreign policy events across thirty European countries alongside in-depth case studies from Denmark, the Netherlands, and Finland. It brings political parties back into the study of foreign policy, demonstrating that the size of the coalition, the ideological proximity of the governing parties, and their relationship with the parliamentary opposition together influence the government's ability to act in the international arena. This book challenges our existing perceptions about the constraints and weaknesses of coalition governments. It sheds new light on the conditions that allow them to act decisively abroad.